Dry slide wear behavior of 601AC/B4C Selective layered functionally graded material with particulate Ni-P coating. (15th January 2020) - Vijay, S; Rao, Ch Srinivasa
Abstract: 601AC/B4 C selective layered Functionally Graded Material with Nickel coating and without Nickel coating is fabricated by powder metallurgy technique. The basic metal alloy powder is made with Mechanical alloying technique. Controlled variables Number of layers (2, 3 and 5 ), particulate size (25 μm and 50 μm ), Load (10 N, 20 N and 30 N), track diameter (60 mm, 80 mm 100 mm), and the speed of the disc (500, 750 and 1000 rpm) are selected to conduct dry sliding wear test using pin on disc apparatus. Experiments are design using Taguchi's L36 orthogonal array. Optimization of parameters is done using Signal-to-Noise ratio. For the wear rate smaller-the-better criteria is used for analyzing the results. Analysis of Variance is done using Minitab software to find the most significant variables for the wear rate. From the results it is concluded that particle condition with 31.49% contribution, number of layers with 30.61% and speed of the disc with 10.36% contribution are the most significant factors. Linear regression equation is developed and conducted confirmation test. From the comparison a 13.5% error is observed between predicted value and actual value. Therefore a quadratic regression equation is proposed to predict the wear rate for this experiment.